2011
DOI: 10.3389/fpsyt.2011.00022
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Substance use, Neurological and Psychiatric Symptoms in Schizophrenia and Substance use Disorder Patients: A 12-Week, Pilot, Case–Control Trial with Quetiapine

Abstract: Neurological and psychiatric symptoms are consequences of substance abuse in schizophrenia and non-schizophrenia patients. The present case–control study examined changes in substance abuse/dependence, and neurological and psychiatric symptoms in substance abusers with [dual diagnosis (DD) group, n = 26] and without schizophrenia [substance use disorder (SUD) group, n = 24] and in non-abusing schizophrenia patients (SCZ group, n = 23) undergoing 12-week treatment with the atypical antipsychotic, quetiapine. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…The HAM-D rates the severity of symptoms observed in depression such as change in mood, insomnia, agitation and weight loss. The HAM-D was administered by a nurse trained by SP, who has vast experience in administration of psychiatric interviews for research purposes [ 29 - 34 ].…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The HAM-D rates the severity of symptoms observed in depression such as change in mood, insomnia, agitation and weight loss. The HAM-D was administered by a nurse trained by SP, who has vast experience in administration of psychiatric interviews for research purposes [ 29 - 34 ].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…This interview-type questionnaire provides measures of overall anxiety, psychological distress (psychic anxiety), and physical complaints related to anxiety (somatic anxiety). The HAM-A was administered by a nurse trained by SP, who has vast experience in the administration of psychiatric interviews for research purposes [ 29 - 34 ].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In SCZ and SUD patients, psychiatric symptoms (positive, negative, and depressive) significantly improved during treatment ( p  < 0.05; for more information, see Zhornitsky et al, 2011). …”
Section: Resultsmentioning
confidence: 97%
“…On baseline, SCZ and SUD patients had similar positive symptoms [SCZ: 17.4 (4.4); SUD: 16.2 (5.1); F  = 3.2; p  = 0.08]; SCZ patients had more negative symptoms than SUD patients [SCZ: 16.9 (4.7); SUD: 13.6 (4.7); F  = 7.2; p  = 0.01]; and SUD patients had more depressive symptoms than SCZ patients [SCZ: 3.6 (4.4); SUD: 6.8 (4.4); F  = 8.4; p  = 0.005; Zhornitsky et al, 2011]. In SCZ and SUD patients, psychiatric symptoms (positive, negative, and depressive) significantly improved during treatment ( p  < 0.05; for more information, see Zhornitsky et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, one study reported that olanzapine was no better than first-generation antipsychotics in the treatment of comorbid drug abuse (Noordsy et al, 2001). Limited information is available about quetiapine or aripiprazole (Brown et al, 2002; Potvin et al, 2008; Zhornitsky et al, 2011). Once more, most of the available information has been generated from case reports, uncontrolled or small controlled studies using different or mixed target substances, making it difficult to reach firm conclusions or provide an adequate basis for comparative analysis.…”
Section: Schizophrenia Comorbid Addictive States and Antipsychoticsmentioning
confidence: 99%